Antimicrobial and wound healing potential of naphthoquinones encapsulated in nanochitosan - Freitas, Cyntia Silva; Pereira, Patricia Ribeiro; Cardoso, Raiane Vieira; Pauli, Fernanda Petzold; Ribeiro, Ruan Carlos Busquet; Da Silva, Fernando De Carvalho; Ferreira, Vitor Francisco; Paschoalin, Vania Margaret Flosi (Frontiers in Bioengineering and Biotechnology, 2024)
The use of chitosan in pharmaceutical formulations is an advantageous approach due to this compound intrinsic biodegradability and biocompatibility, as well as ready availability and low polymer cost. Herein, the naphthoquinones 3-chloromethylene-menadione (NQ1) and 2,3-dichloro-1,4-naphthoquinone (NQ2) were nanoencapsulated into chitosan (CNP) by the ionotropic gelatinization technique. Homogeneous chitosan nanocapsulses of about 193 nm and Z potential ranging from +30.6 to +33.1 mV loaded with NQ1 (CNP-NQ1) or NQ2 (CNPQ-NQ2) were characterized by the DLS, FTIR, SEM, TGA, DSC techniques. With nanoencapsulation efficiencies of ≥ 96%, the solubility of naphthoquinones in aqueous environments was improved, making them suitable for biological system applications. The encapsulated naphthoquinones displayed a controlled release of approximately 80% for CNP-NQ1 and 90% for CNP-NQ2 over an 8 h period at 36°C. Both CNP-NQ1 and CNP-NQ2 retained the already established free naphthoquinone antimicrobial activity against two Staphylococcus aureus strains, Staphylococcus epidermidis, Streptococcus pyogenes and Pseudomonas aeruginosa. Although presenting low toxicity to healthy human cells, only CNP-NQ1 displayed therapeutic indices above 100 for S. aureus and S. epidermidis and above 27 for S. pyogenes and P. aeruginosa, allowing for safe use in human tissues. Furthermore, CNP-NQ1 did not impair the migration of human fibroblast cells in scratch assays, adding promising wound healing properties to this formulation. These findings emphasize that CNP-NQ1 may be useful in protecting injured skin tissue from bacterial contamination, avoiding skin infections not only by reducing bacterial loads but also by accelerating the healing process until complete dermal tissue recovery.